Advancements in Optical Communication Research: A Review of India's Progress - Mandeep Singh; Debanuj Chatterjee; Suchita; Sugeet Sunder; Karamdeep Singh; Mrudula Krishna; Sameer Ahmad Mir; Deepa Venkitesh (IEEE Photonics Journal)
With the increasing use of internet and mobile phones, the capacity of the backbone optical communication link has been continually growing across the world and especially in India. The total optical fiber cable deployed for the BharatNet initiative of Government of India is expected to increase from 3.4 million km to 5 million km in 2024–25 just for providing last-mile connectivity. Considering this deep proliferation, this article attempts to capture the diverse research carried out in India in the domain of optical communication.